2012
DOI: 10.1073/pnas.1115847109
|View full text |Cite
|
Sign up to set email alerts
|

Scientific basis for safely shutting in the Macondo Well after the April 20, 2010Deepwater Horizonblowout

Abstract: As part of the government response to the Deepwater Horizon blowout, a Well Integrity Team evaluated the geologic hazards of shutting in the Macondo Well at the seafloor and determined the conditions under which it could safely be undertaken. Of particular concern was the possibility that, under the anticipated high shut-in pressures, oil could leak out of the well casing below the seafloor. Such a leak could lead to new geologic pathways for hydrocarbon release to the Gulf of Mexico. Evaluating this hazard re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The well could not be left shut in unless the well passed an integrity test (10) that showed that all rupture disks in the well casings and casing shoes had remained intact, despite the explosion. If it had not, shutting in the well would risk release of hydrocarbons to surrounding geologic formations and potential blowouts to the seafloor (Fig.…”
Section: Well Integrity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The well could not be left shut in unless the well passed an integrity test (10) that showed that all rupture disks in the well casings and casing shoes had remained intact, despite the explosion. If it had not, shutting in the well would risk release of hydrocarbons to surrounding geologic formations and potential blowouts to the seafloor (Fig.…”
Section: Well Integrity Testmentioning
confidence: 99%
“…Government and BP experts were weighing whether to proceed with the well integrity test (WIT) (10). Risks identified included (i) broaching of hydrocarbons to the seafloor through multiple subsea floor vents and (ii) sinking of the BOP into the seafloor through liquefaction of surrounding sediments by broaching oil (Fig.…”
Section: Well Integrity Testmentioning
confidence: 99%
“…Not long after the first military applications, acoustic water column mapping with echo sounders was applied to fisheries science, for which the detection and quantification of fish distributions were the primary focus (Kimura, 1929;MacLennan, 1990). The applications of acoustic water column mapping have broadened in recent years to include marine ecosystem acoustics (Benoit-Bird and Lawson, 2016;Godø et al, 2014), observations of gas bubbles and oil droplets associated with natural seeps (Jerram et al, 2015;Merewether et al, 1985), and fossil fuel production (Hickman et al, 2012;. Acoustic imaging of the water column has also been used within the field of physical oceanography; single-beam echo sounders can capture fine-scale oceanographic structures typically attributed to biological scattering or turbulent microstructures (Klymak and Moum, 2003;Pingree and Mardell, 1985;Trevorrow, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic observations from all four NOAA ships made with the lower-frequency echo sounders (12,18, and 38 kHz) often indicated the presence of methane seeps rising from the seafloor (13), a capability that was later exploited during wellhead integrity testing after the well was capped in mid-July (14). Gas bubbles in seawater strongly scatter sound, with scattering cross-sections that are several orders of magnitude higher than a similarly sized oil droplet at frequencies close to the mechanical resonance of the bubble (15).…”
mentioning
confidence: 99%
“…Deepwater Horizon | oil plume | Gulf of Mexico | acoustic remote sensing O n April 20, 2010, an explosion on the Deepwater Horizon drilling rig precipitated an oil spill from a damaged wellhead located approximately 1,500-m below the sea surface, releasing an estimated 7.0 × 10 5 AE 20% m 3 (4.4 × 10 6 barrels) (1) to 7.82 × 10 5 AE 10% m 3 (4.92 × 10 6 barrels) (2) of oil and between 9.14 × 10 9 -1.25 × 10 10 mol of methane (3,4) between April 22 and July 15, 2010 when the well was successfully capped. The depth of the damaged wellhead obscured our collective ability to observe what was happening to the oil as it exited the well, but by mid-May observations of underwater oil plumes were reported (e.g., ref.…”
mentioning
confidence: 99%